Determinants of corporate social and environmental reporting in Indonesia: An analysis from economic, social and political perspectives - Setyorini, Christina Tri (2015)
The objectives of this study are to examine the extent of corporate social and environmental reporting among Indonesian companies and to ascertain its determinants from multiple perspectives: economic, social, and political. The multiple-perspective approach offers alternative interpretations of a similar phenomenon. This study attempts to fill both the theoretical and empirical gaps in corporate social and environmental reporting in Indonesia. It focuses on contentquality and uses a combination of the tools of Clarkson’s environmental index and Sutantoputra’s social index. The sample of this study consisted of 740 observations for five years from 2005 to 2009. Panel data was employed and pooled regression was performed using EViews v.8 to observe the association among the variables of the company characteristics and corporate social and environmental disclosure. Profitability, leverage and size were included as control variables. The results revealed that the level of corporate social and environmental reporting in Indonesia was low. However, the corporate social and environmental disclosure had increased from previous years and was dominated by soft disclosures. The results reported in this study show strong support for the firm’s industry sensitivity, government environmental monitoring, media coverage, strategic posture, government shareholding, foreign activity, leverage and size. Conversely, blockholder ownership, award, and profitability were not supported by this study. Hence, this study has shown that company characteristics can be determined by economic, social, and political perspectives. In this respect, a multiple-perspective approach can help one to take advantage of the complementariness of different theories and gain alternative interpretations of the same phenomenon through a more holistic analysis.